2008
DOI: 10.1111/j.1742-4658.2008.06515.x
|View full text |Cite
|
Sign up to set email alerts
|

d‐Amino acids in the brain: d‐serine in neurotransmission and neurodegeneration

Abstract: N-methyl d-aspartate receptors (NMDARs) are key excitatory neurotransmitter receptors in the brain and are involved in many physiological processes, including memory formation, synaptic plasticity and development [1]. The NMDARs are composed of multiple subunits and their activity is regulated by numerous mechanisms, including different ligands and interacting proteins [2]. The NMDARs display high permeability to Ca 2+ , which is known to play a central role in syn-aptic plasticity and many signal transduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
193
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(205 citation statements)
references
References 98 publications
4
193
0
1
Order By: Relevance
“…In rat brains, the localization of D-amino acid oxidase activity is reciprocal to that of D-serine (8,9), suggesting that D-amino acid oxidase determines the basal levels of D-serine in mammalian brains. However, we have found recently that, in the chicken brain, D-serine is degraded mainly by a D-serine dehydratase (DSD) 4 (10), which catalyzes the ␣,␤-elimination of water from D-serine to form pyruvate and ammonia. In addition, we have found that the chicken DSD (chDSD) has a primary structure similar to those of metal-activated D-threonine aldolases (11)(12)(13), which are fold-type III PLP-dependent enzymes (14), and is distinct from a well known metal-independent bacterial DSD (dsdA) belonging to the foldtype II PLP-dependent enzyme family (14,15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In rat brains, the localization of D-amino acid oxidase activity is reciprocal to that of D-serine (8,9), suggesting that D-amino acid oxidase determines the basal levels of D-serine in mammalian brains. However, we have found recently that, in the chicken brain, D-serine is degraded mainly by a D-serine dehydratase (DSD) 4 (10), which catalyzes the ␣,␤-elimination of water from D-serine to form pyruvate and ammonia. In addition, we have found that the chicken DSD (chDSD) has a primary structure similar to those of metal-activated D-threonine aldolases (11)(12)(13), which are fold-type III PLP-dependent enzymes (14), and is distinct from a well known metal-independent bacterial DSD (dsdA) belonging to the foldtype II PLP-dependent enzyme family (14,15).…”
mentioning
confidence: 99%
“…The NMDA receptor is a glutamate-gated ion channel (3), and glutamate does not activate the receptor unless a co-agonist binding site is simultaneously occupied by D-serine or glycine (4). Because significant concentrations of D-serine exist in vertebrate brains (5), D-serine is believed to physiologically control the sensitivity of the NMDA receptor to glutamate (6).…”
mentioning
confidence: 99%
“…For example, D-serine has been found to modulate the activity of N-methyl-D-aspartate (NMDA) receptor in the brain (6). It is postulated that D-serine binds to the coagonist binding site of the MDA receptor, which is involved in numerous physiological and pathological processes, including synaptic plasticity, learning, memory, neuronal cell migration, and neural diseases (7,8 …”
mentioning
confidence: 99%
“…Furthermore L-Glutamic undergoes the reverse transformation into glutamine under the existence of tissue glutaminase, at the binding ammonia forms. Abovementioned properties of glutamic acid explain its beneficial effect at some central nervous system diseases [7,8]. L-Aspartic plays an important role in the correct function of nervous and endocrine systems and stimulated hormone production (growth hormone, testosterone, progesterone).…”
Section: Study Of Amino Acid Composition Inmentioning
confidence: 99%